Analisis Teori Kekuasaan Michel Foucault atas Propaganda Media dalam Membangun Diskursus Politik - Martinus Barasa; F.X. Armada Riyanto (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This paper aims to examine Foucault's perspective on power in the media as a political tool. The problem focuses on Foucault's thoughts on the relationship between power and knowledge. Power is often seen as a goal or a way of doing politics. With that power, the ruling party is able to control the knowledge system. The media is often a tool used by political rulers to create public opinion. If that opinion has been accepted by many people, then it can be said that the media succeed and the ruler is able to control many people. In order to approach the problem, Foucault's thoughts on the theory of power are used. Data on Foucault's thoughts are obtained from literature obtained through books and journals. Foucault's theory is then used to analyze the role of the media in people's lives, especially in the political field. This study concludes that the media also determines the political direction of certain communities. This political direction is determined by those who have power over the media. The media also has the power to create mass culture in ways that are considered reasonable. Politics as a discourse is used to control in the form of language spread by the media. In the end, knowledge is no longer neutral but has been controlled by the ruling parties.